2018
DOI: 10.7717/peerj.6135
|View full text |Cite
|
Sign up to set email alerts
|

Application of insect-proof nets in pesticide-free rice creates an altered microclimate and differential agronomic performance

Abstract: BackgroundInsect-proof nets are commonly used in crop production and scientific research because of their environmental, economic, and agronomic benefits. However, insect-proof nets can unintentionally alter the microclimate inside the screenhouse and therefore greatly affect plant growth and yield. To examine the microclimate and agronomic performance of pesticide-free rice under insect-proof nets, two-year field experiments were carried out in 2011 and 2012.MethodsIn the present study, the experiment was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…SH is widely used in warm and arid Mediterranean climates (Al-Mulla et al, 2008), this technological adaptation of the productive system allows the construction of an enclosure where the cover and the lateral walls are made of insect screens to limit the entry of some pests, to mitigate the negative effect of severe climates, to reduce the water consumption of the plants, to change the spectrum of the solar radiation and the related physiological benefits, as well as to reduce pesticides applications of, and improve the yield and final quality of the crops (Guo et al, 2015; Villagran & Jaramillo 2020Microclimatic behavior of a screen house... Vidogbéna et al, 2015;Teitel et al, 2017;Mahmood et al, 2018;Mupambi et al, 2018;Yang et al, 2018;Alvarado et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…SH is widely used in warm and arid Mediterranean climates (Al-Mulla et al, 2008), this technological adaptation of the productive system allows the construction of an enclosure where the cover and the lateral walls are made of insect screens to limit the entry of some pests, to mitigate the negative effect of severe climates, to reduce the water consumption of the plants, to change the spectrum of the solar radiation and the related physiological benefits, as well as to reduce pesticides applications of, and improve the yield and final quality of the crops (Guo et al, 2015; Villagran & Jaramillo 2020Microclimatic behavior of a screen house... Vidogbéna et al, 2015;Teitel et al, 2017;Mahmood et al, 2018;Mupambi et al, 2018;Yang et al, 2018;Alvarado et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The growth period of fragrant rice varieties in the present study was about 120 days, and the microclimate of the paddy field could be complicitly varied across days and months [28]. The study by Yang et al [29] showed that the alteration of microclimate had substantial effects on rice agronomic performance. The responses of yield formation of different fragrant rice genotypes to ultrasonic seed treatment also were slightly different.…”
Section: Discussionmentioning
confidence: 88%
“…In the field, variations in climate especially the sudden occurrence of short-term extreme weather, have substantial effects on rice yield [22]. Moreover, the microclimate in paddy fields which is complicated and difficult to measure, also influences yield formation of rice [23]. A stronger antioxidant system in rice ensures stable rice production stabilization.…”
Section: Discussionmentioning
confidence: 99%